Factor structure of the parental reflective functioning questionnaire and association with maternal postpartum depression and comorbid symptoms of psychopathology. - Katrine I Wendelboe (Public Library of Science (PLoS), 2021)
Parental reflective functioning (PRF) refers to the parent's capacity to envision mental states in the infant and in themselves as a parent, and to link such underlying mental process with behavior, which is important for parenting sensitivity and child socio-emotional development. Current findings have linked maternal postpartum depression to impaired reflective skills, imposing a risk on the developing mother-infant relationship, but findings are mixed, and studies have generally used extensive methods for investigating PRF. The present study examined the factor structure and measurement invariance of the Danish version of the 18-item self-report Parental Reflective Functioning Questionnaire (PRFQ) in a sample of mothers with and without diagnosed postpartum depression. Moreover, the association between PRF and maternal postpartum depression in mothers with and without comorbid symptoms of personality disorder and/or clinical levels of psychological distress was investigated. Participants included 423 mothers of infants aged 1-11 months. Confirmatory factor analysis supported a three-factor structure of the PRFQ; however, item loadings suggested that a 15-item version was a more accurate measure of PRF in mothers of infants. Multi-group factor analysis of the 15-item PRFQ infant version indicated measurement invariance among mothers with and without diagnosed postpartum depression. Multinomial logistic regression showed that impaired PRF was associated with maternal psychopathology, although only for mothers with postpartum depression combined with other symptoms of psychopathology. These results provide new evidence for the assessment of maternal self-reported reflective skills as measured by a modified infant version of the PRFQ, as well as a more nuanced understanding of how variance in symptomatology is associated with impaired PRF in mothers in the postpartum period in differing ways.